Some elements of practical classes in students’ of nursing opinions - Walas, Lilla; Fidecki, Wiesław; Adamska-Kuźmicka, Iwona; Sadurska, Agnieszka; Wysokiński, Mariusz; Czekirda, Marta (Nursing Problems / Problemy Pielęgniarstwa, 2008)
Introduction. One of the major elements of marking educational process held by teachers is enabling students to express their opinions about the satisfaction with education. It is an essential part of supervising the quality of education. Aim. The main aim of the pilot study was learning about opinions held by students of 1st degree studies with the reference to realization of first classes conducted in hospital condition. Material and methods. Author’s original opinion pool was used. The results were employed statistical analysis of the data, using c2 test. Conclusions and results. It was discovered that the level of students’ satisfaction with the reference to realization of first classes conducted in hospital condition is average. First classes enable most of the students to verify their decision about occupation choice.